Analisis Fraud Diamond Dalam Mendeteksi Financial Statement Fraud - Rian Abrori; Bullah, Habi; Dwi Amelia, Ananda (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2024)
This study aims to analyze the ability of Fraud Diamond in detecting financial statement fraud in insurance companies listed on the Indonesia Stock Exchange (IDX) in the period of 2013-2017. The Test is performed by using multiple linear regression analysis of financial data from 12 companies. The results showed that financial target (ROA), external pressure (LEV), and nature of industry (RECEIVABLE) proved to be significant in ditecting financial statement fraud, while the financial stability variable (ACHANGE), ineffective monitoring (BDOUT), change in auditor (ΔCPA ), rationalization (TATA), and capability (DCHANGE) not proven to be significant in dtecting financial statement fraud.